2013
DOI: 10.1159/000347177
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension Risk in Patients with Hemoglobin H Disease: Low Incidence and Absence of Correlation with Splenectomy

Abstract: Pulmonary hypertension (PHT) is a common complication for patients with β thalassemia intermediate (TI), especially splenectomized patients. However, the frequency and risk factors of PHT in patients with hemoglobin H (HbH) disease is unknown. The purpose of this study was to identify the prevalence of PHT risk manifested as tricuspid regurgitant jet velocity (TRV) ≥2.5 m/s in patients with HbH disease and its correlation with splenectomy. One hundred and ninety-eight patients with HbH disease who visited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…An elevation of pulmonary vascular resistance cannot be excluded, but is not necessary to explain the mild elevation of TRV seen in the 5 subjects with elevated TRV in our study. Consistent with our findings, a recent study has also reported a very low incidence of possible pulmonary hypertension in HbH subjects [34]. Why pulmonary hypertension appears to be much less common in HbH disease compared to in TI is not known, but nor is it fully understood why pulmonary hypertension is more likely in TI than TM.…”
Section: Discussionsupporting
confidence: 92%
“…An elevation of pulmonary vascular resistance cannot be excluded, but is not necessary to explain the mild elevation of TRV seen in the 5 subjects with elevated TRV in our study. Consistent with our findings, a recent study has also reported a very low incidence of possible pulmonary hypertension in HbH subjects [34]. Why pulmonary hypertension appears to be much less common in HbH disease compared to in TI is not known, but nor is it fully understood why pulmonary hypertension is more likely in TI than TM.…”
Section: Discussionsupporting
confidence: 92%
“…In one study examining pulmonary hemodynamic measurements by echocardiogram in α‐thalassemia patients, only 3/80 (4%) patients with either HgH or Bart's disease had echocardiographic evidence of PH as defined by a TRV greater than 2.9 m/s . In the largest study of HgH patients, out of 198 patients, 13 patients (7%) had TRVs greater than 2.5 m/s as measured by echocardiogram, and only three (2%) of those had TRVs greater than 3.0 m/s . Interestingly, splenectomy was negatively correlated with an elevated TRV, which conflicts with findings in splenectomized β‐thalassemia subjects.…”
Section: Thalassemiasmentioning
confidence: 99%
“…Some studies regarding certain conditions did not show a link (e.g., hemoglobin H disease, hereditary spherocytosis, idiopathic thrombocytopenic purpura) or reported conflicting results (thalassemia) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, many of these studies involved a smaller number of subjects and used noninvasive means to screen for pulmonary hypertension, mainly echocardiography.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The contribution of post-splenectomy thrombocytosis to the observed propensity for coagulation is controversial (6,8,20,36,42,89,106,107). Thrombocytosis is not necessary to develop thromboembolic complications after splenectomy and alone does not explain the procoagulant state (24,27,32,89).…”
Section: The Role Of Post-splenectomy Thrombocytosismentioning
confidence: 99%